FADS1 gene polymorphism(s) and fatty acid composition of serum lipids in adolescents - Metelcová, Tereza; Vaňková, Markéta; Zamrazilová, Hana; Hovhannisyan, Milena; Staňková, Barbora; Tvrzická, Eva; Hill, Martin; Hainer, Vojtěch; Včelák, Josef; Kunešová, Marie (Lipids, 2021)
Polyunsaturated fatty acids (PUFA) influence many physiological functions. Associations have been found between single nucleotide polymorphisms (SNP) in the FADS1 (Fatty acid desaturase 1) gene and the relative abundance of PUFA in serum lipids. This study examines the relationship between two SNPs in the FADS1 gene (rs174546, rs174537) and the fatty acid (FA) composition of serum lipids in adolescents (13-18 years). We used DNA samples (670 children; 336 girls and 334 boys) from the Childhood Obesity Prevalence and Treatment (COPAT) project. Genomic DNA was extracted from peripheral blood leukocytes in whole blood samples. For genotype analysis, TaqMan SNP Genotyping assays (Applied Biosystems) were used. Fatty acid composition of serum lipids was assessed using gas chromatography. The T-statistic and regression were used for statistical evaluations. Minor allele T carriers in both SNPs had significant lower level of palmitic acid (16:0, phospholipids) and arachidonic acid (20:4[n-6], phospholipids) in both sexes. In girls, we found a significant positive association between minor allele T carriers and eicosadienoic acid (20:2[n-6], cholesteryl esters) in both SNPs. Being a minor allele T carrier was significantly positively associated with dihomo-γ-linolenic acid (20:3[n-6], phospholipids) in boys in both SNPs. SNPs (including rs174546, rs174537) in the FADS gene cluster should have impacted desaturase activity, which may contribute to different efficiency of PUFA synthesis.
Keywords: alely; FADS1; Polymorphism, Single Nucleotide; Humans; dítě; rs174537; Child; Pediatric Obesity; jednonukleotidový polymorfismus; Female; Alleles; Genotype; lidé; Delta-5 Fatty Acid Desaturase; fatty acid; desaturasy mastných kyselin; rs174546; mastné kyseliny; ženské pohlaví; obezita dětí a dospívajících; Male; Fatty Acid Desaturases; Adolescent; single nucleotide polymorphism; genotyp; delta-5-desaturasa mastných kyselin; mužské pohlaví; Fatty Acids; mladiství